MANGROVE ECOTOURISM DEVELOPMENT STRATEGY IN KAYU ARA PERMAI VILLAGE, SUNGAI APIT DISTRICT, SIAK REGENCY - Sutopo, Ari Zangga; Kusai, Kusai; Warningsih, Trisla (Asian Journal of Aquatic Sciences, 2022)
This study aims to determine the appropriate strategy in the development of mangrove ecotourism in Kayu Ara Permai Village, Sungai Apit District, Siak Regency. The method used in this research is using purposive sampling technique where the selection is done intentionally based on the criteria that have been determined and determined based on the research objectives. The criteria and respondents who were appointed or selected in this study were the management of the Kayu Ara Permai Village tourist area, Mangrove Ecotourism Tourists in Kayu Ara Permai Village and the Siak Regency Tourism Office. This shows that the appropriate strategy for the development of mangrove ecotourism in Kayu Ara Permai Village, Sungai Apit District, Siak Regency, is the need for publication on social media, sustainable planting of abrasion-resistant mangroves and good cooperation between mangrove ecotourism managers and the community.